Upaya Pencegahan Bullying di Sekolah Perspektif Albert Bandura Dan Thomas Lickona - Askan Nanang Prasetiyo; Gina Kamila; Febrilia Saura Sabrina Rachmania; Moh. Faizin (LPPM IAIN Sorong, 2026)
Bullying remains a systemic problem in school environments, yielding severe negative impacts on both victims and perpetrators. It manifests in physical, verbal, nonverbal, relational, sexual, and cyber forms, potentially triggering trauma, anxiety, depression, decreased academic achievement, and even suicidal ideation. This study aims to analyze and compare bullying prevention strategies in schools from the perspectives of Albert Bandura and Thomas Lickona, evaluating their relevance in creating a character-based educational environment. Employing a qualitative approach through library research, data were gathered from relevant books, scientific journals, articles, and academic documents via documentation studies, and subsequently analyzed using a descriptive-comparative method. The findings reveal that, according to Albert Bandura, bullying behavior is driven by observational learning and imitation (modeling), reciprocal interaction among environment, behavior, and cognition (reciprocal determinism), as well as self-efficacy and reinforcement factors. Conversely, Thomas Lickona emphasizes prevention through character education anchored in three core components: moral knowing, moral feeling, and moral action. The synthesis of both theories suggests that bullying prevention can be optimized by cultivating a positive environment, providing positive role models, instilling moral values and empathy, and strengthening the collaborative roles of parents, teachers, and the community. Ultimately, integrating Bandura's and Lickona's frameworks offers a holistic and effective strategy to build a safe, caring, and bullyingfree school culture.